Aesthetics of Negativity : Blanchot, Adorno, and Autonomy - Allen, William S., 1971- (Book collections on Project MUSE., 2016)
A rigorous and many-layered study of the works of Blanchot and Adorno in terms of the relation between negativity and autonomy in the work of art with particular reference to literature, which yields a thinking of materiality in language as an ambiguous force of critique and innovation.